Twenty-Four-Month Outcome of Gonioscopy-Assisted Transluminal Trabeculotomy (GATT) in Eyes With Prior Corneal Transplant Surgery. Issue 1 (January 2022) - Smith, Oluwatosin U.; Butler, Michelle R.; Grover, Davinder S.; Kornmann, Helen L.; Emanuel, Matthew E.; Godfrey, David G.; Fellman, Ronald L.; Feuer, William
Abstract : Purpose: Glaucoma is a well-known sequelae of corneal transplant surgery and is a leading cause of visual loss in this patient group. We evaluated the performance and safety of gonioscopy-assisted transluminal trabeculotomy (GATT) in this population. Design: Noncomparative retrospective case series. Participants: Consecutive eyes of patients receiving the GATT procedure for uncontrolled intraocular pressure (IOP) following corneal transplant surgery from 2016 to 2019. Methods: Retrospective analysis of eyes with a history of prior corneal transplant undergoing GATT at Glaucoma Associates of Texas between 2016 and 2019 was performed. Data included IOP, patient demographics, preoperative and postoperative medications, preoperative and postoperative corneal procedures, complications, and need for reoperation for IOP control. Main Outcome Measures: IOP reduction and medication use following the procedure. Results: Thirty-nine eyes of 32 patients with prior corneal transplant surgery underwent a GATT procedure. Prior corneal surgery included penetrating keratoplasty (59.0%), Descemet's stripping endothelial keratoplasty (35.9%), Descemet's membrane endothelial keratoplasty (2.6%), and deep anterior lamellar keratoplasty (2.6%). Patient age ranged from 24 to 94 years (mean 68.0 y) with 44% female and 81% Caucasian. The majority of patients had secondary open angle glaucoma (64.1%). There was a significant reduction in IOP and number of medications at all postoperative time points after censoring patients requiring reoperation to control IOP ( P <0.001). At 24 months the pressure decreased from baseline of 30.9±11.5 to 13.9±4.7 mm Hg. Medications decreased from 4.2±1.0 medications at baseline to 0.6±1.0 at 24 months. Visual acuities decreased significantly over the first postsurgical month (all P <0.05), but these recovered at subsequent follow-up visits with 2-Snellen line improvements exceeding losses from month 3 to 36. Seven eyes required reoperation for uncontrolled glaucoma at a median of 8.5 months (range: 1.6 to 16.2 mo) after GATT. The cumulative proportion of eyes undergoing repeat cornea surgery was 2.6%, 2.6%, and 14.3% at 12, 24, and 36 months post-GATT, respectively. Conclusions: This case series describes a group of glaucoma patients, with a history of prior corneal surgery, that were safely and successfully treated with GATT. While classically traditional glaucoma surgeries are considered the standard of care for eyes following corneal transplant surgery, GATT should be considered as a reasonable, safe and effective alternative for surgically lowering IOP.